(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
The purpose of this abstract is to investigate the impact of the RENAL nephrometry score system on operating time, blood loss, and intraoperative complications; the system has been suggested as a method for anatomically classifying renal masses with the aim of predicting surgical outcomes for patients undergoing either partial or radical nephrectomy. Patients and methods: The 36 participants in this prospective study were enrolled at Gazi al Harreri Teaching Hospital between December 2013 and December 2015. In order to manage renal masses, classify them based on their radiological characteristics on MRI and CT scans, and predict the surgical outcome (partial vs. radical nephrectomy), intraoperative blood loss, hospital stay, and intraoperative complications, a renal nephrometry scoring system is utilized. Results: This study included 36 patients who had radical or partial nephrectomy for renal cell carcinoma (RCC). Of them, 17 were male (47.22% of the total) and 19 were female (52.78% of the total). Of the 26 patients who had radical nephrectomy, 13 were female (36.1%) and 13 were male (36.1%). Ten patients had partial nephrectomy, including four men (11.1%) and six females (16.7%). Mild complex scores (4-6), moderate complex scores (7-9), and high complex scores (10-12) were the distribution of nephrometry scores among the sample under study. 5 instances (13.9%) had low scores, 13 cases (36.1%) had intermediate scores, and 18 cases (50.0%) had high scores. Surgery results according to nephrometry score: 10 patients had NSS, 5 had low scores (50%), 3 had moderate scores (30%), and 2 had high scores (20%). For the 26 patients that underwent RN, the results showed that 38.5% had a moderate score and 61.5% had a high score. Aim of study: The purpose of this research is to examine how the RENAL nephrometry scoring system can be used to control renal masses, as well as to forecast postoperative complications, blood loss, and length of hospital stay. Conclusion: For organ-confined renal malignancies, the RENAL nephrometry score was associated with intraoperative complications, EBL, LOS, and surgical prognosis. Evidence like this points to the RENAL nephrometry score as a measure of how technically challenging it is to do a full or partial nephrectomy.